The oxidation behavior of an equimolar FeCoNiCrMn high-entropy alloy at 950 °C in various oxygen-containing atmospheres. (July 2016) - Kai, W.; Li, C.C.; Cheng, F.P.; Chu, K.P.; Huang, R.T.; Tsay, L.W.; Kai, J.J.
Highlights: The oxidation kinetics of the FeCoNiCrMn alloy obeyed a parabolic rate law. The rate constants increased with increasing oxygen pressure, indicative of a typical oxide-scale exhibiting a p-type semiconductivity. Triplex scales formed on the alloy were independent of oxygen pressure. The position of Pt-marker was located at the scale-substrate interface. Abstract: The oxidation behavior of an equimolar FeCoNiCrMn high-entropy alloy was studied in four oxygen-containing atmospheres over the oxygen partial pressure range from 10 to 10 5 Pa at 950 °C. The oxidation kinetics of the alloy followed the parabolic rate law, and the oxidation rate constants increased with increasing oxygen partial pressure. Triplex scales formed on the alloy consisted of an exclusive outer layer of Mn3 O4, a heterophasic intermediate layer of Mn3 O4, (Mn, Cr)3 O4, and Cr2 O3, and an exclusive inner layer of Cr2 O3 .